Theory and Practice of Modern Antenna Range Measurements - Parini, Clive; Gregson, Stuart Fraser; McCormick, John (Lead radar systems engineer); Van Rensburg, Daniël Janse; Eibert, Thomas (IET electromagnetic waves series., 2020)
This two-volume book provides a comprehensive introduction and explanation of both the theory and practice of all forms of modern antenna measurements, from basic assumptions to detailed application scenarios.